Let z be the root of equation x 5 − 1 = 0 with z not equal to 1. compute the value of z 1 5 + z 1 6 + z 1 7 + … + z 5 0 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
How did u factorize the last step???
Log in to reply
My goal was to "extract" 1 + z + z 2 + z 3 + z 4 , knowing that this expression equals 0 . I then noticed I could create groups of five terms at a time by multiplying this expression by z 5 n , 3 ≤ n ≤ 9 , to account for all but the z 5 0 term in the original sequence. It's not the standard way to factorize, but it seemed to be the most efficient way to solve the problem.
Problem Loading...
Note Loading...
Set Loading...
Note first that z 5 − 1 = ( z − 1 ) ( z 4 + z 3 + z 2 + z + 1 ) , so if z 5 − 1 = 0 and z = 1 we have that
z 4 + z 3 + z 2 + z + 1 = 0 .
So we then have that z 1 5 + z 1 6 + z 1 7 + . . . . . . + z 5 0 =
( 1 + z + z 2 + z 3 + z 4 ) ( z 1 5 + z 2 0 + z 2 5 + z 3 0 + z 3 5 + z 4 0 + z 4 5 ) + z 5 0 = z 5 0 = ( z 5 ) 1 0 = 1 1 0 = 1 .